Analysis of a hyper-diverse seed dispersal network: modularity and underlying mechanisms - Donatti, Camila I.; Guimaraes, Paulo R.; Galetti, Mauro [UNESP]; Pizo, Marco Aurellio [UNESP]; Marquitti, Flavia M. D.; Dirzo, Rodolfo (Wiley-Blackwell, 2011)
Mutualistic interactions involving pollination and ant-plant mutualistic networks typically feature tightly linked species grouped in modules. However, such modularity is infrequent in seed dispersal networks, presumably because research on those networks predominantly includes a single taxonomic animal group (e.g. birds). Herein, for the first time, we examine the pattern of interaction in a network that includes multiple taxonomic groups of seed dispersers, and the mechanisms underlying modularity. We found that the network was nested and modular, with five distinguishable modules. Our examination of the mechanisms underlying such modularity showed that plant and animal trait values were associated with specific modules but phylogenetic effect was limited. Thus, the pattern of interaction in this network is only partially explained by shared evolutionary history. We conclude that the observed modularity emerged by a combination of phylogenetic history and trait convergence of phylogenetically unrelated species, shaped by interactions with particular types of dispersal agents.
Keywords: Birds; body mass; complex networks; fish; fruit diameter; mammals; nestedness; phylogenetic analyses; reptiles